Characterization of Thermally Evaporated CdSe1-XSX Thin Films for Solar Cells Applications (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Binary semiconductor CdSe and CdS thin films are widely used for optoelectronic devices and window materials. The formation of ternary CdSe1-xSx thin films improves the physical characteristics of the binary CdSe thin films. The importance of CdSe1-xSx thin film is the change of band gap when incorporating S into the CdSe. This change in energy gap recommends CdSe1-xSx thin film for photovoltaic and photoconductive cells applications. In this work, polycrystalline CdSe1-xSx thin films have been grown in terms of thermal evaporation technique. X-ray diffractometry has been used to determine the lattice parameters and the crystallite size of the CdSe1-xSx mixed crystals. The variation in lattice parameters with composition from x = 0 to x = 1 were linearly. The crystallite size varies parabolically with the change in composition. The energy gap, opt g E , values of CdSe1-xSx thin films were estimated in terms of first derivative of absorbance with respect to wavelength and found to be increased with the formation of the ternary compound Cd-Se-S and with increasing the S content as expense of Se. This wider energy gap of the prepared films, which permits extra light to reach the solar cell junction, was correlated with the change in the microstructure parameters of thin films.